Comparison of Abrasive Wear Resistance of Hardox Steel and Hadfield Cast Steel - Martyna Zemlik; Łukasz Konat; Kacper Leśny; Krzysztof Jamroziak (Applied Sciences)
Among the materials used for components subjected to abrasive wear, chromium cast iron, hardfaced layers, martensitic steels and Hadfield steel should be singled out. Each of these types of materials exhibits a different morphology of structure and strength properties. Hadfield steel, characterized by an austenitic microstructure, shows the ability to strengthen the subsurface layers by cold work, while maintaining a ductile core. Hardox steels belong to the group of low-alloy martensitic boron steels. However, it should be noted that increasing hardness does not always translate into low wear values due to a change in the nature of wear. In view of the above, the authors decided to subject selected Hardox steels and Hadfield cast steels in the post-operational condition to abrasive wear tests in the presence of loose abrasive. The study showed that Hardox Extreme steel exhibits the highest resistance to abrasive wear (value of the coefficient kb is equal to 1.39). In the case of Hadfield steel, the recorded values are slightly lower (kb = 1.32 and 1.33), while the above ratios remain higher compared to Hardox 600 and Hardox 500 steels. The main wear mechanism of high-manganese steels is microploughing, plastic deformation and breakouts of larger fragments of material. In the case of Hardox 450 and Hardox 500 steels, the predominant wear mechanisms are microploughing and breaking out of material fragments. As the hardness of the steel increases, the proportion of wear by microcutting and scratching predominates.